Peta Penanaman Modal Asing (PMA) dan Penanaman Modal Dalam Negeri - Soekarni, Muhammad; Hidayat, Agus Syarip; Suryanto, Joko (Jurnal Ekonomi dan Pembangunan, 2010)
The aim of this paper is to describe the spread of Foreign Direct Investment (FDI) and domestic investment according to its location, sector, and labour absorption. Analysis is based on secondary data published by Indonesia Investment Coordinating Board (BKPM). There are three main findings in this study: First, this study found that in the period 2002-2008, the largest part of FDI or domestic investment. This uneven investment concertration occured because in the eye of investors, Java and Sumatera is more attractive than other island in Indonesia in term of better infrastructure, wider potential market and higher quality of human resources. Second, the majority of foreign and domestic investors selected secondary sector (manufacturing) for their investment. Interestingly, there was a trend that those investments shifted from secondary sector to tertiary sector. Third, labour absorption both in FDI and domestic investment, particulary invetsed in the secondary sector tend to increase. However, there is a tendency that investment in secondary and tertiary sectors moved to less labour intensive industries.